THE RELATIVE AGE EFFECT IN JUNIOR FEMALE BASKETBALL PLAYERS - Silvia POPESCU; Corina ILIN; Csilla GRĂDINARU (Cluj University Press, 2022)
Introduction: Sports activity interferes with physiological growth, adaptability accelerating and perfecting structural, functional and mental differentiation. The performance model is dependent on the total capacity of the players, on the psycho-social system resulting from the perfection of the executive functions, of the morphological, physiological, informational and decisional subsystems. Objective: The objectives underlying this work are the discovery and determination of the relative age effect (RAE) that leaves its mark on the system of failure or success in the lives of athletes, basketball players. By following the birth months of the athletes of a certain year, we try to prove that there is a close connection between the age advance in the life of certain athletes and their career success. The premise of the study is to analyze the impact of the RAE effect in the U16, U18 and U20 categories of the Romanian junior women's basketball teams. Material and method: In order to demonstrate a connection within this subject, the method used was the structuring of sportswomen in several age categories and the analysis of their results. Results: According to the conducted study, the existence of the relative age effect among the selected ones is found, but not in a way that would suggest those born in the first months of the year would have a substantial advantage. Conclusions: The results confirm the fact that there is a possibility for the younger ones to evolve with efficiency similar to their older colleagues.